Increased Th2 activity and diminished skin barrier function cooperate in allergic skin inflammation. Issue 11 (29th August 2016) - Sehra, Sarita; Krishnamurthy, Purna; Koh, Byunghee; Zhou, Hong‐Ming; Seymour, Lee; Akhtar, Nahid; Travers, Jeffrey B.; Turner, Matthew J.; Kaplan, Mark H.
Abstract : Mutations in skin barrier function genes and increased neonatal Th2 responses are risk factors for the development of atopic dermatitis (AD). Using a mouse model of AD, we demonstrate that genetic lesions in these two pathways cooperate in generating a more severe and earlier onset allergic skin inflammation. Abstract : Atopic dermatitis (AD) is a chronic inflammatory skin disease induced by a complex interaction between susceptibility genes encoding skin barrier components and environmental allergen exposure that results in type 2 cytokine production. Although genetic lesions in either component can be risk factors for disease in patients, whether these pathways interact in the development of AD is not clear. To test this, we mated mice with T‐cell specific expression of constitutively active Stat6 (Stat6VT) that spontaneously develop allergic skin inflammation with Flaky tail (Ft) mice that have mutations in Flg and Tmem79 genes that each affect skin barrier function. Our results demonstrate that over 90% of the Stat6VT transgenic mice carrying the Ft alleles (Stat6VTxFt −/− ) develop severe atopic dermatitis lesions by 3–5 months of age, compared with only 40% of Stat6VT mice that develop disease by 6–7 months of age. Further, histopathological analysis of skin tissues from Stat6VTxFt −/− mice revealed extensive thickening of the dermis with increased inflammatory infiltrates as compared with Stat6VT mice. Our study suggests that skin barrier defects and altered Th2 responses independently cooperate in the pathogenesis of allergic skin inflammation, similar to effects observed in patients with AD.